Influence of resin composite insertion technique in preparations with a high C-factor - Duarte Jr., Sillas; Dinelli, Welingtom [UNESP]; Carmona Da Silva, Maria Helena (My University, 2007)
Objective: To evaluate the marginal microleakage in enamel and dentin/cementum walls in preparations with a high C-factor, using 3 resin composite insertion techniques. The null hypothesis was that there is no difference among the 3 resin composite insertion techniques. Method and Materials: Standardized Class 5 cavities were prepared in the lingual and buccal aspects of 30 caries-free, extracted third molars. The prepared teeth were randomly assigned to 3 groups: (1) oblique incremental placement technique, (2) horizontal incremental placement technique, and (3) bulk insertion (single increment). The preparations were restored with a 1-bottle adhesive (Single Bond, 3M ESPE) and microhybrid resin composite (Z100, 3M ESPE). Specimens were isolated with nail varnish except for a 2-mm-wide rim around the restoration and thermocycled (1,000 thermal cycles, 5°C/55°C; 30-second dwell time). The specimens were immersed in an aqueous solution of 50 wt% silver nitrate for 24 hours, followed by 8 hours in a photo-developing solution and evaluated for microleakage using an ordinal scale of 0 to 4. The microleakage scores obtained from occlusal and gingival walls were analyzed with Wilcoxon and Kruskal-Wallis nonparametric tests. Results: The null hypothesis was accepted. The horizontal incremental placement technique, the oblique incremental technique, and bulk insertion resulted in statistically similar enamel and dentin microleakage scores. Conclusion: Neither the incremental techniques nor the bulk placement technique were capable of eliminating the marginal microleakage in preparations with a high C-factor.
Keywords: Adhesion; Adhesive; C-factor; Dentin; Enamel; Resin composite; bisphenol A bis(2 hydroxypropyl) ether dimethacrylate; resin; resin cement; silicon dioxide; single bond; unclassified drug; Z100 composite resin; zirconium; cementation; classification; dental surgery; endodontics; human; methodology; molar tooth; nonparametric test; tooth disease; Bisphenol A-Glycidyl Methacrylate; Cementation; Composite Resins; Dental Cavity Preparation; Dental Leakage; Dental Restoration, Permanent; Humans; Marginal Adaptation (Dentistry); Molar, Third; Resin Cements; Silicon Dioxide; Statistics, Nonparametric; Zirconium